(untitled) (Polish Yearbook of International Law, 2023)
Is the confrontation in Ukraine Putin’s war, or also that of the Russian nation? Can the crimes of the Russian state be hidden in the shadows of Tolstoy or Tchaikovsky? This article distinguishes between the guilt or responsibility of individuals (criminal, political, moral); the international legal responsibility of states; and finally the political, moral, and historical responsibility of nations. In the legal or moral sense, guilt must be individualized. However, the extralegal (political, moral and historical) responsibility (not regulated by law) affects the whole nation and concerns responsibility both for the past and for the future. Nevertheless, if the nation is deemed entirely responsible for the actions of the state or of some national groups, it is not about attributing guilt to the whole nation, but about the collective recovery of the sense of humanity. Thus, suggesting the guilt of the entire nation is based on a misunderstanding. But if the responsibility does not imply guilt, neither does the lack of guilt imply the lack of re- sponsibility. By definition, the moral and political responsibility of the nation does not take a legal (judicial) form. Other forms and instruments are applicable here. In this context such terms as regrets, forgiveness, shame, apologies, or reconciliation appear. Such actions, based on fundamental values, require political courage, wisdom, and far-sightedness. The passivity of the social environment favours the perpetrators of crimes. but does not release the other members of the nation from moral responsibility, and in par- ticular from the obligation to distinguish good from evil. Not all Russians are guilty of crimes, but they all (whether guilty or innocent) bear some moral and political responsibility.